Acitretin induces apoptosis through CD95 signalling pathway in human cutaneous squamous cell carcinoma cell line SCL-1 - Lin, Xiu-Ying (John Wiley & Sons, Ltd, 2009)
Skin cancers are by far the most common human malignancies. Retinoids have shown promising preventive and therapeutic effects against a variety of human malignancies. The aim of this study was to investigate the apoptosis-inducing effect of acitretin on human skin squamous cell carcinoma (SCC) SCL-1 cells. We found that acitretin preferentially inhibited the growth of SCL-1 cells in a dose- and time-dependent manner, but not of non-malignant keratinocyte HaCaT cells. This inhibition appeared to be due to induction of apoptosis as revealed by enzyme-linked immunosorbent assay. AnnexinV/propidium iodide assay and morphological observation confirmed the pro-apoptotic effect of acitretin on SCL-1 cells. We further demonstrated that apoptosis was induced within 1–2 days and involved activation of caspases-8, -9, -3 and poly (ADP-ribose) polymerase (PARP). Caspase-8 inhibitor effectively suppressed acitretin-induced apoptosis whereas caspase-9 inhibitor did not. Acitretin increased the levels of CD95 (Fas), CD95-ligand and Fas-associated death domain. Neutralizing ZB4 anti-Fas antibody significantly inhibited the apoptosis in SCL-1 cells induced by acitretin. These results suggest that acitretin is able to induce apoptosis in skin cancer cells possibly via death receptor CD95 apoptosis pathway without affecting the viability of normal keratinocyte.